The metaphors of political and diplomatic analysts: from a cognitive perspective - Escobar Zapata, Emérita (2012)
In this research we intend to do a study of the metaphorical expressions heard and created in the environment of politicians and diplomats, following the events of September 11, 2001 (11- S), whose responsibility fell on the group Al-Qaeda terrorist. The theoretical model used is that of cognitive semantics developed by George Lakoff and Mark Johnson (1980, 1995, 1999, 2001, 2004), Lakoff and Turner (1989), Lakoff  (1993.1996), Turner and Fauconnier (1995) . This model is ideal for reconstructing the conceptual schemes underlying metaphors or schematic images, created from the interaction between the human mind, body and perceptual-sensory experience or understanding of the world, through the mechanism of categorization. Also interested in explaining the role of these semantic resources in conversations or interceptions carried out these political actors. The reference sources are, first, the book entitled "Bush at War" political analyst, Bob Woodward (2002), second, "Hegemony and Survival" by Noam Chomsky (2003), (2004) and finally, the international press.